1999
DOI: 10.1016/s0014-5793(99)00343-9
|View full text |Cite
|
Sign up to set email alerts
|

Implication of proteasome in estrogen receptor degradation

Abstract: In MCF-7 breast cancer cells, estradiol (E P ) and pure antiestrogen RU 58668 down-regulate the estrogen receptor (ER). Interestingly, the protein synthesis inhibitor cycloheximide (CHX) abrogated solely the effect of E P suggesting a selective difference in the degradation of the receptor induced by estrogenic and antiestrogenic stimulations. A panel of lysosome inhibitors (i.e. bafilomycin, chloroquine, NH R Cl, and monensin), calpain inhibitors (calpastatin and PD 150606) and proteasome inhibitors (lactacys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 45 publications
10
88
0
Order By: Relevance
“…Previous studies have revealed that cycloheximide (CHX) at 50 µM abrogates E 2 -induced ERα degradation by the ubiquitin-proteasome system [33][34][35]. Our investigations extended this finding to all ligands able to induce LxxLL-motif recruitment (data not shown).…”
Section: Lxxll Motif and Erα Level In Mcf-7 Cellssupporting
confidence: 75%
“…Previous studies have revealed that cycloheximide (CHX) at 50 µM abrogates E 2 -induced ERα degradation by the ubiquitin-proteasome system [33][34][35]. Our investigations extended this finding to all ligands able to induce LxxLL-motif recruitment (data not shown).…”
Section: Lxxll Motif and Erα Level In Mcf-7 Cellssupporting
confidence: 75%
“…1991, Dauvois et al . 1992, El Khissiin & Leclercq 1999, Wijayaratne & McDonnell 2001). However, despite the pure antiestrogenic character of fulvestrant, it did not compare advantageously with tamoxifen when used as a first-line therapy for advanced or metastatic breast cancer (Howell et al .…”
Section: Serms Vs Serds: Two Separate Classes Of Antiestrogens?mentioning
confidence: 99%
“…Studies conducted in various laboratories have demonstrated the implication of the ubiquitin-proteasome system (UPS) in the elimination of the mature receptor which has achieved transactivation and has become functionally obsolete (Alarid et al, 1999;El Khissiin, Leclercq, 1999;Laïos et al, 2005;Nawaz et al, 1999a;Wijayaratne, McDonnell, 2001). Natural and pharmacological ligands either accelerate (estrogens, pure antiestrogens) or reduce (partial antiestrogens) the proteasomal degradation of ERα (Laïos et al, 2005;Read et al, 1989;Wijayaratne, McDonnell, 2001) by selecting UPS with high or low degradation rate.…”
Section: Cam Contributes To the To Regulation Of Erα Turnover Ratementioning
confidence: 99%